Managing with Sharia: Strengthening Sharia Banking Spiritual Literation - Said, Salmah; Amiruddin, Andi Muhammad Ali; Asad, Ahmad; Rustan, Cecep; Sofyan, A. Syathir (Jurnal Minds: Manajemen Ide dan Inspirasi, 2019)
The sharia banking main characteristics provide alternative systems by which banks and customers share profits with specific emphasis on fair treatment, ethical investments, and kinship relationship in the production process and avoidance of speculation. Measuring sharia banking performance by applying CAMELS is considered weak in describing non-financial aspects, which shows sharia ethics and the spirituality of sharia banking. Therefore, the ANGELS method can be considered as an alternative one in assessing sharia banking performance. This research applies Bayani, Burhan, and infant epistemological approaches. The result shows that the implementation of sharia principles in sharia banking practice in Makassar still need sharia literacy awareness among sharia banking practitioners since sharia banking is a potential market in the future.